2008
DOI: 10.1002/cbic.200700754
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Genetic Selection System for Improved Enantioselectivity of Bacillus subtilis Lipase A

Abstract: In directed evolution experiments, success often depends on the efficacy of screening or selection methods. Genetic selections have proven to be extremely valuable for evolving enzymes with improved catalytic activity, improved stability, or with altered substrate specificity. In contrast, enantioselectivity is a difficult parameter to select for. In this study, we present a successful strategy that not only selects for catalytic activity, but for the first time also for enantioselectivity, as demonstrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 58 publications
(41 reference statements)
0
29
0
2
Order By: Relevance
“…The major advantage of this structure-based approach is that it allows for the generation of smaller libraries, reducing the time of screening or selection, with higher functional diversity. [8][9][10][11][12] Herein, we describe molecular docking experiments of (R)-1 into the YbfF active site in order to identify active site residues that are in close proximity to the substrate. These docking experiments helped to identify four positions (25, 124, 185 and 235) in the YbfF active site that might be good targets for engineering the enantioselectivity of YbfF towards 1 and 3.…”
Section: Full Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…The major advantage of this structure-based approach is that it allows for the generation of smaller libraries, reducing the time of screening or selection, with higher functional diversity. [8][9][10][11][12] Herein, we describe molecular docking experiments of (R)-1 into the YbfF active site in order to identify active site residues that are in close proximity to the substrate. These docking experiments helped to identify four positions (25, 124, 185 and 235) in the YbfF active site that might be good targets for engineering the enantioselectivity of YbfF towards 1 and 3.…”
Section: Full Papersmentioning
confidence: 99%
“…In the last two decades novel laboratory evolution methods have been devised in order to improve enzyme properties (such as activity, stability and selectivity) towards non-natural substrates. [8][9][10] Random evolution approaches have been the preferred method of choice, since they do not require detailed knowledge of the enzyme structure or reaction mechanism. However, with the increased number of 3D structures solved and the growth of computational methods, structure-based enzyme engineering strategies are becoming more in reach for improving enzyme properties.…”
Section: Full Papersmentioning
confidence: 99%
“…Selection assays are therefore mostly limited for detoxifying enzymes or enzymes synthetizing compounds necessary for cell growth and survival. Selection assays can be designed to screen for enantio-selective enzymes (Boersma et al, 2008, where the desired enantiopure substrate releases essential nutrients upon reaction, while the undesired enantiomer was supplied as an inhibitor or poison releasing substrate, allowing the growth only of the variants having the desired activity.…”
Section: Library Screeningmentioning
confidence: 99%
“…[10] In a follow-up study, they could further refine the principle and identified variants of lipase CAL-B with slightly inverted but not high enantioselectivity towards 1,2-O-isopropylidene glycerol (IPG, WT (wild type): E = 1.9, favoring the (R)-enantiomer to mutants with E = 3-8 favoring the (S)-enantiomer). [11] Similarly, Quax and co-workers [12] investigated a lipase from Bacillus subtilis using IPG, but linked either to aspartate or a phosphonate. Release of the amino acid supported growth of an aspartate auxotroph E. coli strain whereas the phosphonate lead to inhibition of the lipase.…”
mentioning
confidence: 97%